Effect of oil heat treatment on properties of "buluh semantan" (Gigantochloa scortechinii gamble) - Md Salim, Rafidah (2008)
Bamboo is regarded as eco-friendly plant which grows and matures quickly. It has a potential to be used as an alternative raw material to wood. Like wood, bamboo is susceptible to fungal and insect attacks. Heat treatment is one of the potential treatments to enhance the durability of bamboo. In this study, bamboo splits (Gigantochloa scortechinii) were heat-treated in crude palm oil at temperatures ranged from 140 to 220 C for 30 and 60 mins. The objectives were to determine the effect on resistance to fungal and termite attacks, and to assess any significant changes on physical, mechanical and chemical properties of the treated bamboo. The optimum treatment schedule of treating bamboo was also evaluated. The resistance of heat-treated bamboo against white rot fungus (Pycnoporous sanguineus (Pers. Ex Fr.) Murr) and termite (Coptotermes curvignathus Holmgren) was evaluated based on weight loss of sample after exposure to the fungus and termite for 12 weeks and 4 weeks, respectively. For fungal test, the resistance significantly increased when the temperature and time of treatment increase. Heat treatment at 220C/60 min offers the best protection followed by heat treatment at 180C/60 min. A similar trend was also noted for the resistance against subterranean termites. In ground contact test, the most effective treatment condition was at 220C/60 min while the least effective treatment condition was at 140C/60 min. With regard to physical properties; equilibrium moisture content, density and volumetric shrinkage of heat-treated bamboo decreased as the treatment temperature and time increase. Majority of the mechanical properties of bamboo were significantly reduced by the treatments. A significant reduction in values of fibre stress at proportional limit (FSPL), modulus of elasticity (MOE) and shear parallel to grain were recorded when the bamboo were treated at temperature higher than 180C, but for modulus of rupture (MOR), the value was only decreased when it was heated at 220C/60 min. Compression parallel to grain was not affected by the treatments. Holocellulose content of heat-treated bamboo did not differ to each other when it was heated at 180C however, the content reduced significantly when treated at 220C/60 min. Hemicellulose content of bamboo was not affected by the treatments. Cellulose content in bamboo was only reduced when it was treated at temperature higher than 180C. At 140C to 180C, the lignin content in the treated bamboo decreased, but the chemical content value increased when the bamboo was heated at 220C. Starch content in the bamboo was found to be inversely proportional to treatment temperatures. At 180C, duration of treatment did not significantly affect the starch content. As a whole, the optimum treatment condition in protecting bamboo against P. sanguineus and C. curvignathus was 180C/30 min. The mechanical reductions of bamboo found at this condition do not, in general, represent a serious detriment to use.